Functional trait‐based approaches as a common framework for aquatic ecologists - Séverine Martini; Floriane Larras; Aurélien Boyé; Emile Faure; Nicole Aberle; Philippe Archambault; Lise Bacouillard; Beatrix E Beisner; Lucie Bittner; Emmanuel Castella; Michael Danger; Olivier Gauthier; et al. (Limnology and Oceanography, 2021)
Aquatic ecologists face challenges in identifying the general rules of the functioning of ecosystems. A common framework, including freshwater, marine, benthic, and pelagic ecologists, is needed to bridge communication gaps and foster knowledge sharing. This framework should transcend local specificities and taxonomy in order to provide a common ground and shareable tools to address common scientific challenges. Here, we advocate the use of functional trait‐based approaches (FTBAs) for aquatic ecologists and propose concrete paths to go forward. Firstly, we propose to unify existing definitions in FTBAs to adopt a common language. Secondly, we list the numerous databases referencing functional traits for aquatic organisms. Thirdly, we present a synthesis on traditional as well as recent promising methods for the study of aquatic functional traits, including imaging and genomics. Finally, we conclude with a highlight on scientific challenges and promising venues for which FTBAs should foster opportunities for future research. By offering practical tools, our framework provides a clear path forward to the adoption of trait‐based approaches in aquatic ecology.